INDUSTRY OF CATERING: LOGISTICAL AND GEOGRAPHICAL DIMENSION - Igor Smyrnov (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Considered logistical and geographical features of catering – one of contemporary forms of restaurant services. Particular attention is paid to providing catering logistics far from production facilities (or so-called «touring» catering). Proposed as a logistics base of catering package of measures «economical production + six sigma», which covers the system of Kaizen and Gemba Kaizen, (including subsystem 5S), Kanban, ERP, TPM, SMED, VMI, SCM, as well as ICO 9000. Displace essence of social catering and specificity of its logistics.